FIQH SUNDA: DARI IBADAH HINGGA MUAMALAH (JURNAL ALAMIAH, 2022)
Islam entered the Tatar Sunda (West Java) when the people already had customs that were passed down from generation to generation from the ancestors (salaf). Some of the existing customs are forms of worship that emerged from the Sundanese Wiwitan beliefs in this region. Islam with its legal system (fiqh) then entered into dialogue with Sundanese customs to give rise to Islamic Fiqh with a Sundanese flavor. One of these phenomena occurred in the Naga Traditional Village (Tasikmalaya), the Dukuh Traditional Village (Garut) and the Cicarucub Traditional Village (Sukabumi).A study of local fiqh phenomena in three traditional village locations in West Java shows that Islamic Fiqh implemented by the Sundanese people, especially the indigenous community, is a form of acculturation with Sundanese customs. The dynamic nature of Islamic fiqh with one of its fiqh principles "Al-Adah Muhakamah" makes it able to absorb Sundanese customs. While the traditional communities in the three regions have become Muslim, they also don't want to leave their traditions.The researcher brought up the term Sundanese Fiqh as a result of acculturation between Islamic Fiqh and Sundanese customs. This Fiqh has a uniqueness because it is different from the Fiqh of Arabia, Persia, India and other regions. Sundanese Fiqh is a solution for people in West Java to problems that are often the subject of debate regarding Islamic Fiqh and Sundanese customs. He is also a support for the idea of Nusantara Islam, namely Islam that is in harmony with Indonesian culture.